Preferences for an HIV prevention mobile phone app: a qualitative study among men who have sex with men in China - Aidi Zhang; Nancy R. Reynolds; Jason E. Farley; Xiao Wang; Simin Tan; Jin Yan (BMC, 2019)
Abstract Background Men who have sex with men (MSM) have a disproportionate burden of HIV infection. Mobile phone apps provide a promising means of improving HIV prevention among MSM. But this has received little examination in China. The objective of this study was to explore MSM's preferences for an HIV prevention mobile phone app. Methods Qualitative semi-structured personal interviews were conducted with 19 MSM to determine their preferences for features and content to inform the design of an app aimed at HIV prevention in China. Results Five categories were identified under the main category preferences for features of the app: target population, attributes, language used, potential user access, and perceived usefulness. Five categories were identified under the main category preferences for content of the app: functions to facilitate HIV testing behavior, HIV post-exposure prevention, warning against substance use, psychological support, and areas for communication. Conclusions Findings suggest that the design of an app targeting MSM in China should use an integrated framework addressing behavioral and psychological aspects, satisfy common needs of potential users, avoid perpetuating negative stereotypes and stigma, and avoid possible increase of risk behavior due to using the app.